Interpretasi Hamka dan M. Quraish Shihab tentang Ilustrasi Surga - Wendi Parwanto; AbdulGafar Olawale Fahm; Goolam Hussein Rassool; Muhammad Nur Khaliq (Lajnah Pentashihan Mushaf Al-Qur'an, 2025)
The motivation for this study arises from the observation that many commentators still interpret verses illustrating heaven merely as parables, without sufficiently contextualizing them to social reality. Therefore, this study remains necessary, particularly by examining the interpretations of two Indonesian mufassir from different generations: Hamka (a preacher) and Muhammad Quraish Shihab (an academic). This study is library research employing a descriptive-analysis method. The conclusions of this study indicate that both Hamka and Shihab strive to contextualize the interpretation of verses depicting heaven, contextualizing them in sociocultural paradigms and making them relevant to contemporary contexts. However, Hamka and Shihab exhibit different traits and characteristics in their interpretive approaches and narrative constructs. These differences are primarily due to Hamka's active involvement in the world of preaching, whereas Shihab operates within an academic framework. The interpretations of the verses illustrating heaven by both Hamka and Shihab are notably applicable and contextual, making them relevant to the socio-cultural context. Thus, the narratives constructed by Hamka and Shihab render the abstract and metaphysical nuances of these verses more accessible and comprehensible to the public. As Recommendation; it is necessary to create an interpretative framework for metaphysical verses based on Nusantara identity so that it can be easily understood by the audience, especially the Indonesian people.